Efficiency of botanical pesticides against some pests infesting hydroponic cucumber, cultivated under greenhouse conditions - Muhammad Shoaib Saleem (Egyptian Journal of Biological Pest Control, 2019)
Abstract Greenhouse cultivation of vegetables, especially cucumber in hydroponic/soilless culture, has been developed in different parts of the world. There is an expanding interest in hydroponics because they can produce fresh food closer to urban areas. The objective of this study was to evaluate the efficiency of the biopesticides: matrine (extract from Sophora flavescens), spintoram (derived from soil bacterium Saccharopolyspora spinosa), azadirachtin (neem extract), and Annona squamosa (custard apple extract) against the cotton aphid (Aphis gossypii Glov.) and the two-spotted spider mite, (Tetranychus urticae Koch.). A drip-irrigation hydroponics system (DIHS) was designed and used for this study. Fourteen-day-old seedlings of cucumber plants were shifted in DIHS, and nutrient requirements were maintained during the period of experiment. Randomized complete block design (RCBD) was used for this experiment with 3 replicates and with 5 treatments. Data were collected 24 h pre-treatment and 1, 3, 7, and 14 days post-treatment. Results revealed that the custard apple extract showed the highest efficiency (80 and 76%) reduction against the aphid and the mite, respectively, followed by matrine (legend) and neem extract (73%), and spintoram (radiant) (69%) in case of the aphid, while it was followed by matrine (legend) (75%), spintoram (radiant), (66%), and neem extract (56%) in the case of the mite.